VDR polymorphism, gene expression and vitamin D levels in leprosy patients from North Indian population - Singh, Itu; Lavania, Mallika; Pathak, Vinay Kumar; Ahuja, Madhvi; Turankar, Ravindra P.; Singh, Vikram; Sengupta, Utpal (PLOS Neglected Tropical Diseases, 2018)
Author summary Present study was carried out to find out the association of vitamin D receptor (VDR) gene polymorphism, mRNA gene expression of VDR gene and level of vitamin D with leprosy reactions and leprosy patients. Surprisingly, level of vitamin D in leprosy patients was not found to be associated with the disease and its manifestations. VDR genotypes (Fok1 and Taq1) were found to be associated with leprosy patients. t-F-a haplotype was significantly associated with leprosy patients. Gene expression of vitamin D receptor was lower in leprosy patients in comparison to healthy controls.